The Impact of Pay and Job Security on Employee Performance: Examining the Mediating Role of Job Satisfaction for Millennials and Generation Z Employees - Gusti Ayu Widiari Ayunityas Laksmi; Ilman Agung Perdana Putra; Safira Aliya; Abdul Rohman Hafid (Green Publisher Indonesia, 2024)
This study aims to investigate the relationship between key factors influencing employee satisfaction and employee performance for Millennials and Generation Z Employees. The independent variables considered are pay and job security, with job satisfaction regarded as the mediating variable affecting employee performance as the dependent variable. Through careful analysis of empirical data from Millennials and Generation Z Employees, this research explores patterns of relationships among these variables and provides a deeper understanding of their interaction dynamics. The findings of this study are expected to provide valuable insights for human resource management in developing effective strategies to enhance employee satisfaction and overall company performance. Practical implications of the research findings include the development of fair compensation policies, more effective employee development programs, and the creation of a supportive work environment that promotes individual well-being and growth. This research can contribute to the academic literature on human resource management and industrial psychology by enriching our understanding of organizational internal dynamics and providing useful guidance for practitioners to improve their human resource management practices and achieve organizational strategic goals.